2008
DOI: 10.1007/bf03016670
|View full text |Cite
|
Sign up to set email alerts
|

L’hémodilution ne modifie pas les effets vasodilatateurs coronariens de l’oxyde nitrique endogène ou exogène

Abstract: Introduction:It is well known that hemoglobin is a scavenger of nitric oxide (NO). The present study used a canine model to test the hypothesis that acute normovolemic hemodilution (ANH) affects NO-mediated coronary vasodilation.Methods: Studies were performed in 18 open-chest, anesthetized dogs. In Series 1, the contribution of endogenous NO to coronary vasodilatation during ANH with 5% dextran-40 (reduction in hematocrit by 50%) was assessed. This was accomplished by comparing myocardial blood flow (MBF; rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…While the inhibition of nitric oxide production resulted in significant (> 25 mmHg) increases in blood pressure (Table 1) and increased myocardial oxygen extraction at higher hematocrits (>20%) (Figure 4C), L-NAME had essentially no effect on coronary blood flow (Figure 4A) or myocardial oxygen delivery (Figure 4B) at hematocrits ranging from ~30% to ~10%. These data are consistent with the prior studies by Crystal et al in dogs which documented no effect of intracoronary L-NAME on anemic coronary vasodilation down to hematocrits of ~20% [8]. Importantly, the use of intracoronary L-NAME prevented changes in systemic blood pressure and thus argue against hypertension as a confounding influence in the present study.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…While the inhibition of nitric oxide production resulted in significant (> 25 mmHg) increases in blood pressure (Table 1) and increased myocardial oxygen extraction at higher hematocrits (>20%) (Figure 4C), L-NAME had essentially no effect on coronary blood flow (Figure 4A) or myocardial oxygen delivery (Figure 4B) at hematocrits ranging from ~30% to ~10%. These data are consistent with the prior studies by Crystal et al in dogs which documented no effect of intracoronary L-NAME on anemic coronary vasodilation down to hematocrits of ~20% [8]. Importantly, the use of intracoronary L-NAME prevented changes in systemic blood pressure and thus argue against hypertension as a confounding influence in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…It is well established that reductions in hematocrit lead to marked hemodynamic responses including increases in cardiac output, heart rate, contractility, and MVO 2 [8, 30, 37, 64], all of which are important determinants of coronary blood flow [25]. In the present study, we noted significant differences in the coronary response to hemodilution in swine that received volume replacement with saline vs Hespan.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Reports in the literature do not support a major role for NO in hemodilution; however, as previously noted, experimental studies are in general carried out with large levels of hemodilution, usually 50% isovolemic exchanges and in anesthetized animals (5,10). The measurement of nitrite/nitrate concentration showed a tendency to increase with hemodilution; however, the effect was not significant, and how this affects NO bioavailability in the plasma layer is not well established.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, cardiac function was studied using isolated heart preparation and isolated cardiomyocytes, but theses experimental approaches did not truly represent operating conditions of the heart in its physiological environment. Several studies using an open-chest model have reported no statistically significant effects when using NO-releasing agents during isovolemic hemodilution on coronary vasodilation, although myocardial blood flow increased (Crystal, et al 1988,Crystal, et al 2008,Crystal and Salem 1991). Recently, real-time ventricular pressure volume measurements using closed-chest method have been introduced in small animals.…”
Section: Introductionmentioning
confidence: 92%